Estimation of time to recruitment for a three graded system - S, Jayanthi L.; Uma, K. P.; K, Kavithamani. (International Journal of Engineering and Technology, 2026)
A marketing organization consisting of three grades with policy and transfer decisions forming two different sources of depletion is considered. The policy decisions are classified into two different types according to the intensity of attrition. When the policy decisions related to emoluments, benefits and objectives are announced then the exit of personnel is occurred which leads to time overwhelming and expense, so that the recruitment cannot be introduced in real time and also frequent recruitment are not encouraged. When the cumulative loss of manpower on critical occasion cross the level called as threshold, then only the recruitment is introduced and made. In this paper the problem of time to recruitment for this organization is analyzed. when the breakdown threshold, a level of maximum allowable manpower depletion, has three components namely threshold of depletion of manpower, threshold of frequent breaks of existing workers and threshold of backup or reservation of manpower sources. A mathematical model is developed using univarity policy of recruitment based on shock model approach in this paper. The inter-policy decision times and the inter-transfer decision times form same renewal process for three grades to obtain the mean variance of the time to recruitment. Mathematical equations for mean time to recruitment are developed using Laplace transform.